Eketrähallen; sustainability in architectural tectonics by example of a contemporary market hall in Gothenburg - Krafeld, Felix (My University, 2024)
This Master Thesis intents to explore the relationship of tectonic architectural design and the sustainability ambition of architectural design as it is prevalent in the 21st century. The findings of this investigation will be represented in a design proposal of a contemporary market hall, functioning as form of visualization, as well as proof of concept. The basis of the investigation is formed by a definition of terminology of the two to be compared subjects. Here in, the term tectonic, derived from the Greek word „tekton“ for carpenter/ builder, describes an additive design principle focused on detail oriented problem-solving of design challenges. This systematic approach is manifested in design outcomes with a characteristic legibility of structural hierarchy. The current interpretation and implementation of sustainable architectural design is based on academic research, aiming to strategize amongst other things, against global challenges like the destruction of ecosphere, threats to societies through poverty, hunger and lack of healthcare, as well as the need for equal development opportunities for everyone in an at this point, fully globalized world. Initially I would like to hypothesize, that both principles of tectonic design and sustainable architectural design share a need for a practical problem solving approach for a precise and uncomplicated design outcome. Throughout the thesis, I intent to explain why I believe this to be true.
Keywords: tectonic, sustainability